KARAKTERISTIK DAN TIPOLOGI WILAYAH PERI URBAN KECAMATAN JATI AGUNG, KABUPATEN LAMPUNG SELATAN - Nadeak, Venny Putri; Kurnianingsih, Nela Agustin (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
Urban development typically brings changes across physical, social, and economic dimensions. These changes affect both the city's core and its peripheral regions, such as the Jati Agung Subdistrict in South Lampung Regency. As a peri-urban zone near Bandar Lampung City, Jati Agung has experienced significant transformations due to the city's influence. This research aims to identify peri-urban characteristics and typologies based on physical, social, and economic parameters in Jati Agung. The analysis involves quantitative descriptive analysis, scoring, and overlay map analysis. Outcomes from this study reveal that the Jati Agung Subdistrict exhibits peri-urban traits in specific villages. Development across physical, social, and economic facets, however, demonstrates non-uniformity throughout the entire area. Villages portraying peri-urban characteristics still lean towards a more dominant rural profile. Typological classification, considering physical, social, and economic aspects, results in two categories within the Jati Agung Subdistrict: secondary peri-urban and rural peri-urban. Six villages manifest secondary peri-urban characteristics, and fifteen villages exhibit rural peri-urban characteristics. The results indicate that as of 2023, the impact of Bandar Lampung City development has not significantly altered the rural characteristics of Jati Agung's villages, as no primary peri-urban areas were identified in the typology.